Extracellular Vesicle-Encapsulated miR-29b-3p Released From Bone Marrow-Derived Mesenchymal Stem Cells Underpins Osteogenic Differentiation - Zhang, Xueliang; Wang, Wenji; Wang, Yongping; Zhao, Haiyan; Han, Xingwen; Zhao, Tong; Qu, Peng (Frontiers in Cell and Developmental Biology, 2021)
Objective Mesenchymal stem cells (MSCs) confer therapeutic benefits in various pathologies and cancers by releasing extracellular vesicles (EVs) loaded with bioactive compounds. Herein, we identified bone marrow MSC (BMSC)-derived EVs harboring microRNA (miR)-29b-3p to regulate osteogenic differentiation through effects on the suppressor of cytokine signaling 1 (SOCS1)/nuclear factor (NF)-κB pathway via targeting of lysine demethylase 5A (KDM5A) in osteoporosis. Methods We quantified the miR-29b-3p in BMSC-derived EVs from bone marrow specimens of osteoporotic patients and non-osteoporotic patients during total hip arthroplasty (THA). miR-29b-3p targeting KDM5A was confirmed by promoter luciferase assay, and enrichment of KDM5A in the promoter region of SOCS1 was analyzed by chromatin immunoprecipitation (ChIP). The expression and translocation of NF-κB to the nucleus were detected by western blot analysis and immunofluorescence staining, respectively. An ovariectomized (OVX) osteoporosis mouse model was established to further confirm the in vitro findings. Results BMSC-derived EVs of osteoporotic patients exhibited downregulated miR-29b-3p. EV-encapsulated miR-29b-3p from BMSCs potentiated osteogenic differentiation by specifically inhibiting KDM5A. KDM5A inhibited osteogenic differentiation by the regulation of H3K4me3 and H3K27ac of SOCS1. SOCS1 potentiated osteogenic differentiation by inhibiting NF-κB pathway. Conclusion EV-encapsulated miR-29b-3p derived from BMSCs potentiated osteogenic differentiation through blockade of the SOCS1/NF-κB pathway by inhibition of KDM5A.